IMPLEMENTASI NILAI-NILAI PENDIDIKAN KARAKTER DALAM PEMBIASAAN PEMBACAAN ASMAUL HUSNA PADA APEL PAGI DI MTS BI’RUL ULUM GEDANGAN SIDOARJO - Moch. Hasan Sidqi; Eli Masnawati (Rihlah Review: Jurnal Pendidikan Islam, 2025)
The purpose of this research is to find out the values ​​of character education at MTs Bi'rul Ulum Gedangan Sidoarjo, to find out the implementation of character education values ​​in the habit of reading Asmaul Husna at morning assembly and to find out the supporting and inhibiting factors for the implementation of character education values ​​in the habit reading Asmaul Husna at the morning assembly at MTs Bi'rul Ulum Gedangan Sidorjo. The method used is a descriptive qualitative method which produces results that MTs Bi'rul Ulum Gedangan Sidoarjo instills character values ​​such as religious obedience, integrity, honesty, etc. through various programs, one of which is the habit of reading the Asmaul Husna at morning assembly to foster student discipline. Even though it is supported by student motivation, teacher control, infrastructure, and parents, inhibiting factors such as lack of control outside class hours, differences in parental awareness, and student participation need to be minimized so that the implementation of character education runs effectively.